CULTURAL ARCHAEOLOGY: TEXT – CODE – SYSTEM OF REPETITIONS AND KEY-NAMES - Artyom V. Drobyshev (Russian Studies in Culture and Society)
Various interdisciplinary studies, linking approaches of culturology and archaeology, allow to consider one of the productive directions within this convergence, called culturology of archeology. This direction focuses on the study of archaeological memorials and texts that can act as cultural phenomena, which allows to comprehensively study the nature of such phenomena, their structure, laws of development and functioning in modern society. The article aims to clarify the content of this interdisciplinary area, highlight its research potential.